Vascular Endothelial Growth Factor-A(165)b Restores Normal Glomerular Water Permeability in a Diphtheria-Toxin Mouse Model of Glomerular Injury - Stevens, Megan (Nephron Clin Pract, 2018)
BACKGROUND/AIMS: Genetic cell ablation using the human diphtheria toxin receptor (hDTR) is a new strategy used for analysing cellular function. Diphtheria toxin (DT) is a cytotoxic protein that leaves mouse cells relatively unaffected, but upon binding to hDTR it ultimately leads to cell death. We used a podocyte-specific hDTR expressing (Pod-DTR) mouse to assess the anti-permeability and cyto-protective effects of the splice isoform vascular endothelial growth factor (VEGF-A(165)b). METHODS: The Pod-DTR mouse was crossed with a mouse that over-expressed VEGF-A(165)b specifically in the podocytes (Neph-VEGF-A(165)b). Wild type (WT), Pod-DTR, Neph-VEGF-A(165)b and Pod-DTR X Neph-VEGF-A(165)b mice were treated with several doses of DT (1, 5, 100, and 1,000 ng/g bodyweight). Urine was collected and the glomerular water permeability (L(p)A/V(i)) was measured ex vivo after 14 days. Structural analysis and podocyte marker expression were also assessed. RESULTS: Pod-DTR mice developed an increased glomerular L(p)A/V(i) 14 days after administration of DT (all doses), which was prevented when the mice over-expressed VEGF-A(165)b. No major structural abnormalities, podocyte ablation or albuminuria was observed in Pod-DTR mice, indicating this to be a mild model of podocyte disease. However, a change in expression and localisation of nephrin within the podocytes was observed, indicating disruption of the slit diaphragm in the Pod-DTR mice. This was prevented in the Pod-DTR X Neph-VEGF-A(165)b mice. CONCLUSION: Although only a mild model of podocyte injury, over-expression of the anti-permeability VEGF-A(165)b isoform in the podocytes of Pod-DTR mice had a protective effect. Therefore, this study further highlights the therapeutic potential of VEGF-A(165)b in glomerular disease.